Is it all about the feeling?: Affective and (meta-)cognitive mechanisms underlying the truth effect [ataset] - Stump, Annika; Voß, Andreas; Rummel, Jan (Universität, 2021)
This data-set contains all data from the paper "Is it all about the feeling? Affective and (meta-)cognitive mechanisms underlying the truth effect."
Deposit date: 2020-05-18
Gesehen am 16.02.2021
Keywords: Forschungsdaten; Datenbank